2015
DOI: 10.1186/s40510-015-0098-5
|View full text |Cite
|
Sign up to set email alerts
|

Timetable for oral prevention in childhood—a current opinion

Abstract: Dental caries in young children remains a public health problem particularly for children whose families are socioeconomically deprived. A child's first dental visit should be at approximately 12 months of age and this should facilitate the provision of anticipatory guidance concerning oral health and dental development to the child's parents/guardians. Compliance with dietary advice is of key importance and motivational interviewing shows promise in relation to parents adopting good oral health practices for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
2
12
0
1
Order By: Relevance
“…The correlation between ECC and nursing requires additional debate ( 11 , 12 ). These study results illustrate the prominent protective role played by healthful dietary practices in preschool children, which is consistent with the results of other authors ( 2 , 3 , 20 33 ). The benefits of water and unsweetened milk, sandwiches and fresh fruit have been proven; this view still holds even after dietary habits conducive to caries have been introduced to the statistic model including the presence of sugar in a child's diet and too frequent consumption of snacks and sweet beverages.…”
Section: Discussionsupporting
confidence: 93%
“…The correlation between ECC and nursing requires additional debate ( 11 , 12 ). These study results illustrate the prominent protective role played by healthful dietary practices in preschool children, which is consistent with the results of other authors ( 2 , 3 , 20 33 ). The benefits of water and unsweetened milk, sandwiches and fresh fruit have been proven; this view still holds even after dietary habits conducive to caries have been introduced to the statistic model including the presence of sugar in a child's diet and too frequent consumption of snacks and sweet beverages.…”
Section: Discussionsupporting
confidence: 93%
“…Optimal oral hygiene requires thorough and clear professional instructions, adequate tools, and patient motivation, which is an essential factor to obtain compliance [2, 3]. A systematic review of randomized controlled trials conducted by Gao and colleagues [4] showed varied success in using motivational approaches, which are potentially more useful to achieve behavioral changes than conventional health education, focusing on disseminating information and giving normative advice.…”
Section: Introductionmentioning
confidence: 99%
“…According to another study from Iowa, USA, of 340 parents who completed questioners, 2% reported having taken their child for a dental visit by one year of age, 11% by two years of age, and 31% by three years of age [11]. In contrast, a study in four communities within Manitoba, Canada, reported that 74.7% of caregivers (guardians and majority being mothers) favored a dental visit by the age of one year [17]. In general, apart from the latter study, all of the listed studies are in accordance with findings concerning the first period of our research: about 10% or even less children visited the dentist in the first year of their life.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, a gynecologist can present the importance of a mother's state of oral cavity for the child's development, early childhood caries development, transmission of the oral infection, etc., but can also point out the importance of the first dental visit. Furthermore, the presence of the dental staff at prenatal classes is necessary to introduce the concept of the early dental visit and to increase the awareness of the overall importance of oral and dental health as part of general health [17].…”
Section: Introductionmentioning
confidence: 99%